2017
DOI: 10.1016/j.chemphys.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular hydrogen-bonding effects on O H stretch overtone excitation for fluorinated hydroperoxides

Abstract: Applying computational methods for predicting gas-phase O-H stretch overtone spectra to the series of fluorinated hydroperoxides CF 3 OOH, CHF 2 OOH, and CH 2 FOOH reveals how intramolecular hydrogen bonding changes their overtone photochemistry, relative to their un-fluorinated analog CH 3 OOH. Intramolecular hydrogen bonding between fluorine and the hydroxyl hydrogen atom decreases O-H stretch frequencies and raises the barrier for torsion about the O-O bond. Whereas O-O torsion accompanies O-H stretch overt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Cao et al discovered a red shift of the FTIR spectra in the FEC-containing electrolyte compared with the FEC-free electrolyte because of the intermolecular interaction with the fluorine compounds . Many reports confirmed that the hydroxyl groups on the metal oxide surface have a high capability to form hydrogen bonds on the surface. Moreover, the strong hydrogen bonding between the organic fluorine atom and the hydroxyl group in the form of OH···F interactions has been widely reported. Hence, in our case, we speculate that NaF can form hydrogen bonding with the hydroxyl groups in amorphous TiO 2 , which shares the electrons surrounding the fluorine in F-organics bonds . Therefore, the electron cloud density surrounding the fluorine for participating the F organic bonds will decrease.…”
Section: Discussionsupporting
confidence: 51%
“…Cao et al discovered a red shift of the FTIR spectra in the FEC-containing electrolyte compared with the FEC-free electrolyte because of the intermolecular interaction with the fluorine compounds . Many reports confirmed that the hydroxyl groups on the metal oxide surface have a high capability to form hydrogen bonds on the surface. Moreover, the strong hydrogen bonding between the organic fluorine atom and the hydroxyl group in the form of OH···F interactions has been widely reported. Hence, in our case, we speculate that NaF can form hydrogen bonding with the hydroxyl groups in amorphous TiO 2 , which shares the electrons surrounding the fluorine in F-organics bonds . Therefore, the electron cloud density surrounding the fluorine for participating the F organic bonds will decrease.…”
Section: Discussionsupporting
confidence: 51%